Penyuluhan Penggunaan Media Pembelajaran Calistung untuk Meningkatkan Minat Belajar Siswa - Yukti Sari, Rospala Hanisah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Learning media is the empowerment of all instruments created to make it easier for teachers to convey learning material and students to understand learning concepts. This service activity aims to increase students' interest in learning by implementing Calistung learning media. This activity was carried out at SD Negeri 1 Kereng Bangkirai, Palangkaraya City and MIS Fathul Iman Palangkaraya and was attended by teachers and students. The result of this activity is that there is an increase in students' interest in learning when applying Calistung learning media in class, which is marked by increased student enthusiasm during the learning process.